Preparedness of special needs school communities for earthquakes: A case study in an area with a very high seismicity in Daerah Istimewa Yogyakarta - Satmoko, Tranggono Aji; Satyarno, Iman; Saputra, Ashar (ASEAN Natural Disaster Mitigation and Education Journal, 2024)
Background: DIY is a province in Indonesia that is very susceptible to earthquakes. In 2006, a seismic event measuring 6.2 on the moment magnitude scale struck DIY, causing injuries and extensive damage to both the structural and non-structural elements of several buildings, including one in the education sector. The problem of structural damage to educational facilities is a significant worry, especially in school communities that cater to vulnerable children, such as those in special needs schools/Sekolah Luar Biasa (SLB), who are more susceptible to harm during disasters. This study aims to assess the level of preparedness and accessibility of the special needs school community located in a very high seismic region of earthquakes in the DIY, in the event of an earthquake. Methods: The structural assessment took the form of a binary question, requiring a simple yes or no response. Findings: To reduce the risk of earthquakes in the special needs education sector, a review of the preparedness of the special needs school building and community was carried out by implementing “Satuan Pendidikan Aman Bencana (SPAB)” or Disaster Safe Education Unit guidelines. The findings suggest that SLB Sekar Melati Muh. Imogiri (78.26) was classed as having moderate earthquake risk, whereas SLB Dharma Bhakti Piyungan (88.55), SLB Insan Mandiri Dlingo (90.29), and SLB Purworaharjo (88.41) featured infrastructure that was rated as very vulnerable. With respect to SLB Dharma Bhakti Piyungan (64.52), SLB Insan Mandiri Dlingo (60.11), and SLB Purworaharjo (76.94), their average community readiness index scores put them in the intermediate capability category for earthquake preparedness. SLB Sekar Melati Muhmmadiyah Imogiri, however, was categorized as having a low capacity for earthquake readiness with an average index score of 56.92 for community preparedness. Conclusion: special needs school communities should raise their level of preparedness by undertaking seismic socialization and regular simulations to boost the community's understanding of earthquakes and reduce the likelihood of harm following an earthquake. Novelty/Originality of this Study: The study breaks new ground by assessing earthquake preparedness and accessibility in special needs schools within a high-seismicity region, addressing a critical gap in disaster risk reduction for vulnerable populations.